2021
DOI: 10.3390/ijerph18147692
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factor and Disease Measures from the Population Assessment of Tobacco and Health (PATH) Study

Abstract: Background: Cardiovascular disease is a key health condition associated with tobacco use; however, clinical measures are not typically possible in population-based studies. In this paper, we assess the reliability and validity of self-reported cardiovascular risk factors and diseases in a large nationally representative study of tobacco use and health outcomes. Methods: This paper analyzes self-reported cardiovascular risk factors and disease among adults age 40 years and older based on U.S. nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Another potential limitation to note is that these findings are based on participants’ self-reported CVD and tobacco use. However, our previous study of CVD among adults age 40 years and older using the PATH Study data established the concurrent validity and reliability of these self-reported measures of CVD [ 18 ]. Potential additional analyses might link a measure of biochemical verification of self-reported tobacco use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential limitation to note is that these findings are based on participants’ self-reported CVD and tobacco use. However, our previous study of CVD among adults age 40 years and older using the PATH Study data established the concurrent validity and reliability of these self-reported measures of CVD [ 18 ]. Potential additional analyses might link a measure of biochemical verification of self-reported tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who reported that they had been told they had CHF, stroke, or heart attack at a subsequent wave were classified as having an incident CVD. Our previous analyses of self-reported CVD among adults age 40 years and older using the PATH Study data established the concurrent validity and reliability of measures of CVD [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…34 While atrial fibrillation and chronic heart failure, which are known risk factors of cardiovascular disease and death in the general population, have been shown to have a relationship with incident VTE. [36][37][38][39][40] Therefore, to efficiently deal with the prevention of CVDT after VTE, physicians should pay particular attention to early identification and management of these conditions. Despite the fact that this was not the primary aim of our study, we also explored the role of anticoagulant treatment in our study on the risk of CVDT, and we found in univariable and multivariable analyses that the risk of CVDT was significantly reduced for patients treated with DOACs (vs. VKAs, 83% of risk reduction in multivariable analysis) and for patients treated for a longer duration (3-12 vs. 0-3 months,57% of risk reduction in multivariable analysis; >12 vs. 0-3 months, 67% of risk reduction in multivariable analysis).…”
Section: Risk Factors Of Cvdtmentioning
confidence: 99%
“…The validity and reliability of self-reported MI, HF, and stroke were supported previously within the PATH study sample. 5 Cox regressions were used to model incident composite CVD outcomes as a function of a 4-category cigarette and e-cigarette use exposure measure. Respondents contributed a maximum of 4 years of follow-up time from baseline (wave 1) until a CVD diagnosis, loss to follow-up, or the end of follow-up (wave 5), whichever came first.…”
mentioning
confidence: 99%
“…The validity and reliability of self-reported MI, HF, and stroke were supported previously within the PATH study sample. 5…”
mentioning
confidence: 99%